Social and economic empowerment of women through handicrafts - Mahfuj, Numan; Ritu, Tajri Jahan; Rahman, Md. Arifur; Arafat, Md. Abdur Rahman (Indonesian Journal of Social Sciences, 2025)
Handicrafts have provided employment opportunities to thousands of rural women in Bangladesh. By creating earning capacities, engagement with this industry can help these women improve their access to social and economic resources. This paper focuses on the social and economic conditions of the women involved in the handicraft industry while also addressing the barriers women encounter in this handicraft industry. This study follows both qualitative and quantitative approaches and collects primary data from 20 women owners and 120 women workers of handicraft businesses in Jamalpur District, Bangladesh, through interviews and questionnaires. A multi-stage sampling technique was followed to collect data from the sampled participants. The study found that handicrafts have significantly empowered rural women both socially and economically. However, the barriers like low wages, excessive increases in prices of raw materials, unawareness among the handicraft workers about the training institutions and their functions, unavailability of training programs to all levels of women involved in the handicraft industry, lack of capital, exclusion of small entrepreneurs from government incentives have greatly affected the further flourishment of women involved in handicrafts. If these barriers are resolved, handicrafts can play a very important role in the social and economic empowerment of women.